DESEMPENHO DA VENTILAÇÃO NATURAL EM DIFERENTES CONFIGURAÇÕES DE MUROS VAZADOS LAMINADOS - Costa, Isabely; Barbosa, Ricardo; Barbirato, Gianna (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The wall, with its physical and symbolic dimensions, is an element present in Brazilian housing. From the perspective of environmental comfort, it represents an obstacle to the free movement of the winds. Thus, the insertion of porous elements can be configured as an interesting resource to reduce the negative effect provided by this component. In this sense, the present paper had as objective to evaluate the performance of the natural ventilation produced by different configurations of laminated porous walls. Computational Fluid Dynamics (CFD) was used as methodology. Three typologies of walls were simulated, applied in a popular dwelling model. The results showed that the models of porous walls, for the most part, presented gains in behavior patterns and wind speeds in the leeward of the wall, compared to the values of the model without openings, especially the configurations with vertical blades and with softer slope. Despite the increase in velocity rates, it was found that, in most cases, this increase did not generate satisfactory conditions of thermal comfort. Evidencing that the most permeable wall, like any other element constructed, must be planned, because depending on the geometry, it can have different performances, even, inferior to the totally closed wall.